Relevansi Isu Mutakhir Kesenjangan Sosial Pada Pembelajaran Bahasa Dan Sastra Indonesia - Manelly, Yas; Lestari, Frida Nur; Syofiani, Syofiani; Morelent, Morelent (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2025)
The learning of Indonesian language and literature is closely related to the reality of human life. Not only good teaching and correct language skills, language and literature are also able to reflect social conditions such as educational gaps, culture, and other societal problems. Based on this, the purpose of writing this article is to describe the relevance of the latest issue of social disparity in education to the learning of Indonesian language and literature. The method used in this study is a literature study by collecting information and news related to education gaps, especially in terms of facilities and access to learning, in the period from 1 to 30 May 2025. The data was then analysed and associated with the implementation of Indonesian language and literature learning. The findings show that the issue of social disparities in education, such as differences in facilities between schools, and unequal access to technology, has relevance in Indonesian language learning. This happens because these social realities can be used as material for reflection, teaching materials, and learning evaluation. The conclusion of this article emphasizes that the learning of Indonesian language and literature cannot be separated from the dynamics of people's lives, so the issue of social disparities in education is important to be raised in a contextual and meaningful learning process.